Morphological changes on the hard palatine mucosa of rats (Rattus norvegicus albinus) after chronic alcohol consumption - Martinez, M.; Martinez, F. E.; Watanabe, I. (My University, 1998)
In order to examine the effects of alcohol on the hard palatine mucosa of rats, sixty adult female rats (Rattus norvegicus albinus) were divided into two experimental groups. The control group received solid diet (Purina rat chow) and tap water ad libitum. The alcoholic group received the same solid diet and was allowed to drink only sugar cane brandy dissolved in 30% Gay Lussac (v/v). At the end of periods of 90, 180 and 270 days of treatment, the animals at estro were sacrificed and the hard palatine mucosa were prepared for TEM and SEM methods. The basal cells of the alcoholic groups (90, 180 and 270 days of treatment) demonstrated some alterations: the intercellular spaces between these cells were higher, presented cytoplasmatic lipid droplets and autolysis. Also, the connective tissue showed intense lipid droplets accumulation in the alcoholic groups. These modifications suggested that chronic alcohol ingestion was able to modify the integrity of the cells in the rat hard palatine mucosa.
Keywords: Alcohol; Connective tissue; Epithelium; Paldtine mucosa